The Effect of Product Quality, Price, and Word of Mouth on Packing Sticker Purchase Decision at CV. Blitz Media Kreasindo Pekanbaru City - Amirudin M. Amin; Rika Angelia; Mukhsin; Pujiono Eddy; Rangga Rahmadian Yuliendi (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the effect of product quality, price, and word of mouth on packing sticker purchasing decisions. This research will object of research is all consumers who visit CV. Blitz Media Kreasindo Pekanbaru. In this study, the object of research is all consumers who visit CV. Blitz Media Kreasindo Pekanbaru. The number of samples in this study was determined from the opinion of